Analisis Pengaruh Gaya Kepemimpinan Terhadap Kinerja Staf Pelayanan Medis Dan Paramedis Di RSUD Tarempa Kepulauan Anambas Riau - Zulhendri Zulhendri; Ismail Efendy; Ramadhani Syafitri Nasution (Jurnal Rumpun Ilmu Kesehatan, 2024)
There are many factors that influence employee or employee performance at work. that performance is basically influenced by many factors, one of which is work motivation in carrying out tasks. One of the factors that can influence employee performance is work motivation, incentives (compensation), and leadership. The aim of this research is to determine and analyze the influence of leadership style on the performance of medical and non-medical service staff at Tarempa Hospital, Anambas Islands, Riau in 2024. This type of research uses a descriptive analytical survey with a cross-sectional design. The population in this study was all the medical and non-medical service installation staff at Tarempa Regional Hospital, Anambas Islands, Riau, totaling 78 people. While the sample numbered 78 people, this population sampling was carried out with the total population. Data analysis was carried out using univariate, bivariate and multivariate analysis. Based on the results of the chi-square test, it is known that the performance of medical and non-medical service staff has an influence on Militaristic Leadership Style, Paternalistic Leadership Style, Laissirez Fair Leadership Style and Democratic Leadership Style p = 0.000, meaning that there is an influence of Militaristic Leadership Style, Paternalistic Leadership Style, Leadership Style Laissirez Fair and Democratic Leadership Style. on the performance of medical and non-medical service staff. From the results of the multivariate analysis, it is known that the most influential variable in this study is the Democratic Leadership Style variable with an odds ratio (OR) value of 62,850 which predominantly influences medical and non-medical service staff. The conclusion in this research is that the appropriate leadership style applied by medical and non-medical services is a democratic leadership style. This is because based on research results, democratic leadership style is the most dominant influence on the performance of medical and non-medical service staff. It is recommended that medical and non-medical service staff strive to improve the performance of medical and non-medical services through reading and discussion activities and discipline when entering work.